Mexican American Mojo : Popular Music, Dance, and Urban Culture in Los Angeles, 1935-1968 - Macias, Anthony F. (Book collections on Project MUSE., 2008)
A study of the creation of jazz, swing, and R & B music within the multicultural, multiethnic terrain of Los Angeles during and after World War II.